IL-6 and Type 2 Diabetes - Almelan, Maha F. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: Interleukin -6 (IL-6) as the key mediator of the acute phase reaction is of interest .elevated protein concentrations of IL-6 in the blood have been shown in patients with type 2diabetes. This study aimed to investigate the association of IL-6 and type 2 diabetes. Materials and Methods: Blood samples were collected from 40 patients with type 2 diabetes and 40 person apparently healthy control were examined for IL-6 level by Enzyme Linked Immune Sorbent Assay. HbA1c determined by high pressure liquid chromatography .total cholesterol, HDL cholesterol and triglyceride were determined enzymatically. Other risk factors study like age, sex and BMI.Results: results shows that IL-6 was higher in patients than in control (p